2013
DOI: 10.2134/agronj2012.0385
|View full text |Cite
|
Sign up to set email alerts
|

Land Application of Aluminum Water Treatment Residual to Bahiagrass Pastures: Soil and Forage Responses

Abstract: Phosphorus transport is an environmental concern, particularly in coarse‐textured soils with minimal P‐sorbing capability. This 2‐yr study evaluated the impact of an Al water treatment residual (Al‐WTR) application on soil P responses, leachate P concentrations, and bahiagrass (Paspalum notatum Flüggé) yield and nutritive value. Treatments were a factorial combination of three Al‐WTR levels (0, 35, and 70 Mg ha–1) and two methods of application (surface vs. incorporated), replicated four times in a randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Similarly, Codling et al (2002) found that WTR application rates of 50 g kg −1 decreased water-soluble P and Mehlich 3-extractable phosphorus concentration by 98-99% and 87-90% respectively. Likewise, Silveira et al (2013) found that the treatments trialled (30 and 75 t ha −1 ) reduced water-extractable P in soil A and E horizons by more than 60% (e.g. 18.4 mg kg −1 in control soil A horizon, down to 7.3 and 2.8 mg kg −1 in 35 and 70 t ha −1 treatments respectively).…”
Section: Immobilisation Of Contaminants and Excess Nutrients In Soilmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, Codling et al (2002) found that WTR application rates of 50 g kg −1 decreased water-soluble P and Mehlich 3-extractable phosphorus concentration by 98-99% and 87-90% respectively. Likewise, Silveira et al (2013) found that the treatments trialled (30 and 75 t ha −1 ) reduced water-extractable P in soil A and E horizons by more than 60% (e.g. 18.4 mg kg −1 in control soil A horizon, down to 7.3 and 2.8 mg kg −1 in 35 and 70 t ha −1 treatments respectively).…”
Section: Immobilisation Of Contaminants and Excess Nutrients In Soilmentioning
confidence: 85%
“…In order to address these issues, Zohar et al (2017) produced a WTR-organic composite that could potentially find use as a slow-release P fertiliser; this was achieved by initially using WTRs to treat soil leachate and dairy wastewater to remove P. A 9-week desorption experiment found that P was slowly released, initially at a rate of 30 mg kg −1 , which decreased to 10 mg kg −1 after 28 days and remained constant until the experiment concluded at 60 days. However, this preparation may not always be necessary as Silveira et al (2013) highlighted that WTRs were an adequate substitute for organic-rich fertiliser in all but P-deficient soils when growing bahiagrass (Paspalum notatum Flüggé).…”
Section: Immobilisation Of Contaminants and Excess Nutrients In Soilmentioning
confidence: 99%
“…The relatively lesser total annual herbage accumulation in 2017 observed in the inorganic fertilizer treatments may be the result of the excessive rainfall experienced in August and September 2017, which may have resulted in significant N losses. Because the majority of the N present in the inorganic fertilizer is more easily susceptible to leaching, most likely bahiagrass total annual herbage accumulation was negatively affected from the excessive rainfall with the application of inorganic fertilizer (Silveira et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Contamination risks for recycling of wastes in agricultural soils must be assessed. They include accumulation of potentially toxic elements (PTEs) (Mossa et al, 2020; Wasserman et al, 2018), whereas WTR is commonly highlighted by presenting high total content of Al, Fe, and Mn which may generate deleterious effects on plant growth (Kluczka et al, 2017; Lombi et al, 2010; Silveira et al, 2013). In addition, loads of pathogenic organisms in BS must be monitored and kept under safe levels (Pereira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%